Prediction of a magnetic Weyl semimetal without spin-orbit coupling and strong anomalous Hall effect in the Heusler compensated ferrimagnet Ti2MnAl - Shi, Wujun; Muechler, Lukas; Manna, Kaustuv; Zhang, Yang; Koepernik, Klaus; Car, Roberto; Van Den Brink, Jeroen; Felser, Claudia; Sun, Yan (Physical Review B, 2018)
We predict a magnetic Weyl semimetal in the inverse Heusler Ti2MnAl, a compensated ferrimagnet with a vanishing net magnetic moment and a Curie temperature of over 650 K. Despite the vanishing net magnetic moment, we calculate a large intrinsic anomalous Hall effect (AHE) of about 300 S/cm. It derives from the Berry curvature distribution of the Weyl points, which are only 14 meV away from the Fermi level and isolated from trivial bands. Different from antiferromagnets Mn3X (X=Ge, Sn, Ga, Ir, Rh, and Pt), where the AHE originates from the noncollinear magnetic structure, the AHE in Ti2MnAl stems directly from the Weyl points and is topologically protected. The large anomalous Hall conductivity (AHC) together with a low charge carrier concentration should give rise to a large anomalous Hall angle. In contrast to the Co-based ferromagnetic Heusler compounds, the Weyl nodes in Ti2MnAl do not derive from nodal lines due to the lack of mirror symmetries in the inverse Heusler structure. Since the magnetic structure breaks spin-rotation symmetry, the Weyl nodes are stable without SOC. Moreover, because of the large separation between Weyl points of opposite topological charge, the Fermi arcs extent up to 75% of the reciprocal lattice vectors in length. This makes Ti2MnAl an excellent candidate for the comprehensive study of magnetic Weyl semimetals. It is the first example of a material with Weyl points, large anomalous Hall effect, and angle despite a vanishing net magnetic moment.
CRIS-Team Scopus Importer:2022-04-14